Entrepreneurial Behaviour of Upland Program Recipient Livestock Farmers in The Central Java Province, Indonesia, Based on Modified Planned Behaviour Theory - Danang Nur Cahyo; Krismiwati Muatip; Mochamad Sugiarto; Yusmi Nur Wakhidati; Tri Rachmanto Prihambodo; Lis Safitri; Indra Sugiharto; Akhlis Rahman Sari Nurhidayat (Buletin Peternakan, 2026)
Traditional farmers need to improve their capabilities and adopt entrepreneurial behaviour to enhance the productivity and competitiveness of livestock businesses. This study aims to analyse the entrepreneurial behaviour of farmers participating in the Upland Program in Central Java using the Theory of Planned Behaviour (TPB), and to identify the key factors influencing this behaviour. As an added novelty, this research applies a modified TPB framework to evaluate entrepreneurial behaviour among livestock farmers within a government-supported rural development program—an approach that has rarely been explored in the Indonesian context. The study was conducted in two purposively selected regencies, Purbalingga and Banjarnegara, which represent local livestock development centres and are recipients of the Upland Program. The minimum sample size was determined using the G*Power application, and 166 farmers were interviewed with a structured questionnaire. Data were analysed descriptively and statistically using the Partial Least Squares Structural Equation Model (PLS-SEM) approach. The findings indicate that farmers’ characteristics, attitude, perceived behavioural control, and intention fall into the medium category, while subjective norms and entrepreneurial behaviour fall into the medium-high category. Attitude and perceived behavioural control significantly affect both intention and entrepreneurial behaviour, whereas subjective norms do not show a significant influence. Differences in location also result in variations in farmers’ intentions and entrepreneurial behaviour. These results highlight the importance of strengthening farmers’ attitudes and perceived behavioural control, particularly through intensive assistance and capacity-building initiatives. Enhancing these factors is expected to encourage stronger entrepreneurial behaviour among livestock farmers, ultimately contributing to improved productivity and overall welfare.